TheLevel of Using Islamic Education Omani Teachers' the Classroom Questioning Strategies - Mohammad Abdulkareem Al-Ayasrah (Sultan Qaboos University, 2011)
The study aimed at identifying the Islamic education Omani teachers' level of using the classroom questioning strategies. To achieve this aim, the data was collected by a checklist of seven dimensions and (45) items strategies. After ensuring its validity and reliability, the instrument was distributed to (34) male and female Omani teachers. The main findings of the study were: • Four dimensions obtained relatively high means of the questioning strategies' importance and three dimensions obtained relatively average means of the importance of the questioning strategies. • There are no significant differences at the level(α  = ,05) in the Islamic education teachers' use of the classroom questioning strategies attributed to the type of the topic of the lesson. • There are significant differences among teachers due to gender variable in favor of females. • The findings also showed significant differences attributed to the classroom in all the whole instrument in general and in the dimension of 'appropriateness' in particular in favor of grade five. • It also showed significant differences in all dimensions due to the teachers experience in favor of teachers of little or an average teaching experience. The researcher provided some recommendations in the light of the result.